Miről álmodik a lelkipásztor? Telegdi T. István alpestesi lelkész álomfeljegyzései - ŐSZ, Sándor-Előd (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2017)
What Does a Reformed Pastor Dream of? The Notes of István T. Telegdi, Reformed Pastor of Alpestes about His Dreams. The study deals with the description of the dreams of a Reformed pastor who worked at the beginning of the 17th century. In the episcopal library of Székesfehérvár can be found one issue from the 1590 edition of Andreas Hondroff's work with the title Theatrum Historicum... We know a few possessors of this book: András Keczeli dominie in Tövis, Gábor Csernátoni pastor in Marosillye then in Alpestes and István Telegdi T. pastor also in Alpestes. On the book Gábor Csernátoni wrote the birth date of his children and István Telegdi wrote down ten of his dreams. The description of these dreams contains numerous cultural aspects and details about the mentality of that period – in three dreams figures Gábor Bethlen prince of Transylvania and in one the widow of the Moldavian prince, Marcu Cercel.